Assessment of antibacterial efficacy of a biocompatible nanoparticle PC@AgNPs against Staphylococcus aureus. (January 2019) - Ananda, A.P.; Manukumar, H.M.; Krishnamurthy, N.B.; Nagendra, B.S.; Savitha, K.R.
Abstract: A plant, Priva cordifolia mediated silver nanoparticle was prepared and characterized by UV-Vis spectroscopy, fourier-transform infrared spectroscopy (FT-IR), energy dispersive X-ray (EDX), scanning electron microscopy (SEM), transmission electron microscopy (TEM), dynamic light scattering (DLS) and x-ray diffraction (XRD) analysis. The minimum inhibitory concentration of the synthesized nanoparticle against Staphylococcus aureus was found to be 100 ± 0.80 μg/mL with 9.38 ± 0.04 mm zone of inhibition. The bactericidal activity was shown primarily due to membrane damage evident from SEM, atomic force microscopy (AFM), potassium efflux, cellular material leakage, and bio-electrochemical changes in electron transport chain data. It was also of interest to find PC@AgNPs interfering with biofilm formation by S.aureus, assessed qualitatively by SEM, confocal laser scanning microscopy (CLSM) and quantitatively by dye staining method. The bio-compatibility of PC@AgNPs was established by anti-coagulant, thrombolytic, partial thromboplastin time, thrombin-like activity and fibrinolytic activity that suggested its good maintenance of hemostatic conditions. PC@AgNPs also prevented the coagulation of rabbit plasma which as per the standard drug Dabigatran reaction was indicative of the down-regulation of virulence Coa gene expression. Graphical abstract: Highlights: Bactericidal effect of PC@AgNPs on Staphylococcus aureus established by SEM, AFM, fatty acid profile and ion efflux data. The nanoparticle also exhibits anti-biofilm property, evidenced by SEM, CLSM and dye staining method. The anti-coagulase activity with drug Dabigatran indicated down regulation of Coa gene validating anti-bacterial activity. Bio-compatibility of the nanoparticle was amply demonstrated at hemostatic level.